Pendidikan Gender dalam Buku Perempuan, Islam, dan Negara Karya K.H. Husein Muhammad - Andri Wijaksono; Ahmad Shofiyuddin Ichsan (AN NUR: Jurnal Studi Islam, 2022)
The gender gap in education was mostly caused by gender socialization in schools and the presence of a hidden gender bias curriculum. One of the indicators that could be noticed was when male and female students sometimes received different education. Therefore, the researcher aimed to analyze what were the values of gender education in the book Perempuan, Islam, dan Negara (Women, Islam and the State) by K.H Husein Muhammad and how the relevance of the book was to gender education in the contemporary era. This type of study was library research with a philosophical approach. The results of the study showed that the values of gender education in the book Perempuan, Islam, dan Negara included: the equality of women and men before Allah Swt, the existence of rights and opportunities for women and men in education, the existence of equal rights and obligations for women and men in work, there was equal status for women and men in the eyes of the law. Its relevance in the current era included: gender education was able to provide equal justice and equality within the scope of schools and society, gender education could be realized equally to all elements of society, gender education seeked to improve the quality of students towards gender development in Indonesia.